The Activity of Long-tailed Macaque (Macaca fascicularis) at Plantation Forest in Ogan Komering Ilir Regency, South Sumatera - Tiara Wulandari; Arum Setiawan; Pandu Sapta Nugraha (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
Long-tailed macaque (Macaca fascicularis) is a quite adaptive animal so it could be found in a diverse range of habitat types, one of the habitats is Plantation Forest on peatlands. This study aims to obtain the information about the activity of long-tailed macaque related to habitat utilization at Plantation The operational activities in the Plantation Forest can affect the activities of long-tailed macaque, changing of food sources, and they have a potential to attack the Acacia plants, so it’s necessary to do research about the activity of long-tailed macaque related to the habitat utilization at Plantation Forest and to acknowledge the types of plants used by long-tailed macaque for food and shelter. This research is a descriptive study and the data are obtained through a focal animal sampling method in April and May 2019 at the Plantation Forest in Sungai Penyabungan District, Ogan Komering Ilir Regency. The focal animal sampling method used at 7.00-17.00 WIB with using interval of 10 minutes. Based on the study, the long-tailed macaque used the active time to feed (24.60%), rest (25.58%), move (27.92%), and social activities (21.89%) included vocalization, agonistic, and grooming. The vegetation parts consumed by the long-tailed macaque are leaves (42.30%), fruits (34.62%), and flowers (23.08%). The vegetation used as food is Acacia crassicarpa, Melaleuca cajuputi, and Melastoma malabathricum. The plant that’s most often used as food and shelter is Acacia crassicarpa.